PERAN KEPEMIMPINAN KEPALA SEKOLAH DASAR PEREMPUAN DALAM MENINGKATKAN KEDISIPLINAN GURU (STUDI KASUS DI SD NEGERI BATURSARI 7 KECAMATAN MRANGGEN KABUPATEN DEMAK) (Solidarity: Journal of Education, Society and Culture, 2013)
Institution failures and successes are decided by the leader. A headmaster leadership becomes a guide and a purpose of a school. The leader of an education centre in this case which is led by female. A leadership way that has been applied by this female headmaster is a democratic leadership in increasing teacher’s discipline. This research uses qualitative method. The research takes place at SD Negeri Batursari 7. The subjects of the research are the headmaster and six teachers at SD Negeri Batursari 7. The methods used for collecting data are observation, interview, and documentation. The data validity that is used is trianggulasi data technique. The analysis method consists of data collecting, data reduction, data service, and the conclusion. The result of the research shows that the female headmaster’s leadership of SD Negeri Batursari 7 applies the democratic leadership. The role of female elementary school headmaster’s leadership in increasing teachers’ dicipline is by giving sample of dicipline activities, such as : the headmaster goes to school early in the morning, motivating the teachers, personally approaching the teachers, giving compliment for teacher’s success and supervision for monitoring the teacher tasks. The problems that are faced by female headmaster in increasing teacher’s dicipline is divided into two factors, they are internal factor (the headmaster’s lackness of confident in leading the teachers ), and external factor (this comes from teacher’s skills).